Coal mine waters in South Africa: Their Geochemistry,quality and classification. Volume one and two - Azzie, Bernadette Ann-Marie (Department of Geological Sciences, 2024)
South Africa is thought to be one of the few water-scarce countries in the world in which coal mining has been, and still is, extensively performed. Parts of Australia and the U.S.A. (specifically Wyoming and Montana) are also water-scarce coal-mining regions. In the past, mining has impacted heavily on the South African environment (Funke, 1983). In recent years, however, individual mines have been striving to ensure that the negative impacts of their operations are kept within acceptable limits, especially in terms of water conservation. Numerous problems are known to exist specifically in the coal mining industry where water is required for underground and surface operations. In these operations it is used for drilling, dust suppression, environmental cooling, as an energy source in hydropower and as a transport medium for backfilling. In addition, potable water is required for drinking purposes. Large volumes of water are affected by chemical contaminants in the coal mines (Azzie, 1999). These contaminants vary significantly depending on the coal seam mined, the mining method employed, the area, size and purpose of the infrastructure used. The water management structures in place around the seam, the chemistry of the rock sequence in which the coal is found and the quality and quantity of the natural groundwater also play a role (Kempe, 1983).